Letting Go of Narrative History: The Linearity of Time and the Art of Recounting the Past - Ari Helo (European Journal of American Studies)
This paper argues that we can let go of the conception of narrative history, not because we know history to be something else entirely, but because the conception too often leads to needless confusion about the methodological basics of historical research among both history students and professional historians themselves. One may view history simply as knowledge of the past and as an ongoing discussion between historians (and other interested parties) over the best account of any given past phenomenon. Given that we politically disagree on where exactly history has brought us, the safest epistemological position for a practicing historian is that the past is just as messy as our own present in which we attempt to find political solutions for a better future. Rather than clinging to any inherently narrative character of history, or of historical representation, the practicing historian may well concentrate on explaining the meaning of a given phenomenon in the past and its possible historical significance for the present, and at least attempt to distinguish between these two.